2011
DOI: 10.1039/c0nj00612b
|View full text |Cite
|
Sign up to set email alerts
|

3-Substituted xanthines as promising candidates for quadruplex formation: computational, synthetic and analytical studies

Abstract: Our computational studies suggest that 3-substituted xanthines are good candidates for tetrad and quadruplex structures. 3-Methylxanthine (3MX) has been synthesized from 7-benzylxanthine, and the existence of tetrameric and octameric aggregates of 3MX with NH 4 + , Na + and K + ions in the gas phase (MS) and in DMSO-d 6 solution (NMR) has been observed. The ''internal'' H-bonds (N1HÁ Á ÁO6) are stronger than the ''external'' ones (N7HÁ Á ÁO2) in these clusters (NMR). Fig. 1 Tetrads composed of 7H-3-methylxanth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(60 citation statements)
references
References 46 publications
2
57
0
Order By: Relevance
“…A range of noncovalent clusters with different cations are observed in the gas phase, in agreement with Szolomájer et al [10]. When ammonium acetate is added as a solvent modifier, abundant peaks correspond to tetrameric species with alkali metal and ammonium cations ( Figure 1a); for example [(3-MX) 4 [10,12,13] by many singly (Figure 1a), doubly (Figure 1b-d), and multiply (Figure 1d) charged species, making it difficult to identify which species are present because of the overlapping isotopic patterns.…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…A range of noncovalent clusters with different cations are observed in the gas phase, in agreement with Szolomájer et al [10]. When ammonium acetate is added as a solvent modifier, abundant peaks correspond to tetrameric species with alkali metal and ammonium cations ( Figure 1a); for example [(3-MX) 4 [10,12,13] by many singly (Figure 1a), doubly (Figure 1b-d), and multiply (Figure 1d) charged species, making it difficult to identify which species are present because of the overlapping isotopic patterns.…”
Section: Resultssupporting
confidence: 79%
“…3-MX has been studied by electrospray ionization mass spectrometry (ESI-MS) and nuclear magnetic resonance by Szolomájer et al [10]; mass spectral data for a single tetrameric complex of 3-MX (or tetrad) and an octameric species composed of two parallel tetrads were reported. Here we report a study using ESI combined with a prototype FAIMS device and orthogonal acceleration time-of-flight (TOF) MS, to investigate noncovalently bound, supramolecular complexes of (3-MX) n .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that the complex damaged the sequences by photobridging intramolecularly two or more G bases with the metallic [(tap) 2-Ru(tpac)Ru(tap) 2 ] 4+ . We designed three new complexes [Ru(bpy) 2 (biim)] 2+ (1), [Ru(phen) 2 (biim)] 2+ (2) and [Ru(p-mopip) 2 -(biim)] 2+ (3), all the three complexes have bisimidazole as the main ligand (Scheme 1). 22 Thomas et al reported that the dinuclear tppz-based systems could bind with high affinity to quadruplex DNA at high ionic strengths through the 22-mer d(AG 3 3 ] human telomeric sequence.…”
Section: Introductionmentioning
confidence: 99%
“…[51][52][53][54][55] Generally conditions for Bn group removal entail use of 10% Pd/C catalyst at >40 bar and >40°C, [52][53][54][56][57][58] with Cbz groups are amenable to removal at lower temperatures and pressures. [51][52][53][54][55] Generally conditions for Bn group removal entail use of 10% Pd/C catalyst at >40 bar and >40°C, [52][53][54][56][57][58] with Cbz groups are amenable to removal at lower temperatures and pressures.…”
Section: Hydrogenolysis Of Alcohols and Aminesmentioning
confidence: 99%